Tal1NXtc01 in Xanthomonas translucens pv. cerealis Contributes to Virulence in Bacterial Leaf Streak of Wheat - Shah, Syed Mashab Ali; Haq, Fazal; Ma, Wenxiu; Xu, Xiameng; Wang, Sai; Xu, Zhengyin; Zou, Lifang; Zhu, Bo; Chen, Gongyou (Frontiers in Microbiology, 2019)
Xanthomonas translucens pv. cerealis (Xtc) causes bacterial leaf streak (BLS) of important cereal crops, including wheat (Triticum aestivum) and barley (Hordeum vulgare). Transcription activator-like effectors (TALEs) play vital roles in many plant diseases caused by Xanthomonas spp.; however, TALEs have not been previously characterized in Xtc. In this study, the whole genome of NXtc01, a virulent strain of Xtc from Xinjiang, China, was sequenced and compared with genomes of other Xanthomonas spp. Xtc NXtc01 consists of a single 4,622,298 bp chromosome that encodes 4,004 genes. Alignment of the NXtc01 sequence with the draft genome of Xtc strain CFBP 2541 (United States) revealed a single giant inversion and differences in the location of two tal genes, which were designated tal1 and tal2. In NXtc01, both tal genes are located on the chromosome, whereas tal2 is plasmid-encoded in CFBP 2541. The repeat variable diresidues (RVDs) at the 12th and 13th sites within Tal2 repeat units were identical in both strains, whereas Tal1 showed differences in the third RVD. Xtc NXtc01 and CFBP 2541 encoded 35 and 33 non-TALE type III effectors (T3Es), respectively. tal1, tal2, and tal-free deletion mutants of Xtc NXtc01 were constructed and evaluated for virulence. The tal1 and tal-free deletion mutants were impaired with respect to symptom development and growth in wheat, suggesting that tal1 is a virulence factor in NXtc01. This was confirmed in gain-of-function experiments that showed the introduction of tal1, but not tal2, restored virulence to the tal-free mutant. Furthermore, we generated a hrcC deletion mutant of NXtc01; the hrcC mutant was nonpathogenic on wheat and unable to elicit a hypersensitive response in the nonhost Nicotiana benthamiana. Our data provide a platform for exploring the roles of both TALEs and non-TALEs in promoting BLS on wheat.